2007
DOI: 10.1037/0002-9432.77.3.454
|View full text |Cite
|
Sign up to set email alerts
|

Children's self-reports about violence exposure: An examination of the Things I Have Seen and Heard Scale.

Abstract: Children's exposure to violence is often found to be an important predictor of child outcomes. The measures most frequently used to assess it have not been systematically examined, and there is little consensus about how to use these measures. This study examined a version of the Things I Have Seen and Heard Scale in a sample of 784 children who completed the scale at both age 6 and 8. There was only modest support for the use of the scale as a set of single-item measures or as a simple sum of items. Explorato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 49 publications
1
17
0
1
Order By: Relevance
“…Sixteen mothers reported on services received by family members that were not reported by the target youth. Other studies also have found discrepancies between parent and youth reports in terms of exposure to violence (Lewis et al, 2010;Thompson et al, 2007), and youth psychiatric symptoms (Hawley & Weisz, 2003;Thompson et al, 2006). This discrepancy may reflect that family members may not talk openly about mental health issues, especially with minors, or that parents, not youth, are responsible for mental health care of other family members.…”
Section: Discussionmentioning
confidence: 89%
“…Sixteen mothers reported on services received by family members that were not reported by the target youth. Other studies also have found discrepancies between parent and youth reports in terms of exposure to violence (Lewis et al, 2010;Thompson et al, 2007), and youth psychiatric symptoms (Hawley & Weisz, 2003;Thompson et al, 2006). This discrepancy may reflect that family members may not talk openly about mental health issues, especially with minors, or that parents, not youth, are responsible for mental health care of other family members.…”
Section: Discussionmentioning
confidence: 89%
“…Including parent-report measures in our study might have provided a different set of perspectives into children's peer relationships and corresponding distress; however, parent-reports of exposure to violence are frequently inaccurate because parents may be unaware of violence that their child has witnessed (Buka et al 2001;Martinez and Richters 1993;Thompson et al 2007). It is difficult to determine the severity of the violent acts to which children have been exposed (Berman et al 1996).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, children are asked about physical harm, muggings, and sexual assault. Various versions (e.g., young child, older child, and parent-report) of this measure have been used in several epidemiological studies, including those conducted by the National Institute of Mental Health Richters and Martinez 1993), and it is the most commonly used measure for assessing children's exposure to violence (Thompson et al 2007). Whereas other samples have had a coefficient alpha slightly above .80 (e.g., Dempsey 2002), the alpha for our sample was .91.…”
Section: Methodsmentioning
confidence: 99%
“…Community violence exposure among caregivers was assessed through a modified version of the Things I Have Seen and Heard Scale, which has been shown to be valid and modestly reliable among children over a 2-year period (Thompson et al, 2007). Caregivers indicated whether each of 10 community-based events (e.g., heard gun shots) occurred since the time they had been caring for the participating child (0=never), as well as the number of times each occurring event had taken place (1=once, 2=twice, 3=three times, 4=four or more times).…”
Section: 0 Methodsmentioning
confidence: 99%